2016
DOI: 10.1007/s12520-016-0430-0
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for lapis lazuli provenance determination: evidence for an Afghan origin of the stones used for ancient carved artefacts kept at the Egyptian Museum of Florence (Italy)

Abstract: ▶ Covers the full spectrum of natural scientific methods with an emphasis on the archaeological contexts and the questions being studied ▶ Bridges the gap between archaeologists and natural scientists Archaeological and Anthropological Sciences covers the full spectrum of natural scientific methods with an emphasis on the archaeological contexts and the questions being studied. It bridges the gap between archaeologists and natural scientists providing a forum to encourage the continued integration of scientifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 26 publications
0
29
0
Order By: Relevance
“…They allow for analysing single crystals of different mineral phases, a fundamental aspect in a heterogeneous material as lapis lazuli, and they are non-invasive, a necessary feature since it is impossible to take samples from artworks. In this study, different markers were found and proposed to distinguish among the four possible provenances: Afghanistan (Badakhshan), Tajikistan (Pamir Mountains), Siberia (near Lake Baikal), and Chile (Ovalle) [45].…”
Section: Technological Advance: the Micro-pixe Technique At The Infn-...mentioning
confidence: 99%
“…They allow for analysing single crystals of different mineral phases, a fundamental aspect in a heterogeneous material as lapis lazuli, and they are non-invasive, a necessary feature since it is impossible to take samples from artworks. In this study, different markers were found and proposed to distinguish among the four possible provenances: Afghanistan (Badakhshan), Tajikistan (Pamir Mountains), Siberia (near Lake Baikal), and Chile (Ovalle) [45].…”
Section: Technological Advance: the Micro-pixe Technique At The Infn-...mentioning
confidence: 99%
“…This last feature is mainly due to the adoption of external beam setup, where both detectors and sample are maintained out of vacuum, thus avoiding/limiting effects such as heating, selective sublimation/evaporation, charging etc. This technique has been used for CH to study many different samples, such as paintings [28][29][30][31][32][33][34], metal point drawings [35,36], precious [37][38][39][40] and semi-precious stones [41][42][43][44][45], ancient coins [46][47][48], precious metals [49][50][51][52], ancient bronze statues [53,54], terracotta, pottery, and clay [55][56][57][58][59], and ancient manuscripts [60][61][62][63].…”
Section: X-ray Detectors-pixementioning
confidence: 99%
“…The research has been focused in searching markers on single mineral phases using microscopic techniques, which allow to observe and to analyse single crystals in a non-invasive way. On the basis of the markers found, a protocol was established [25] in which the luminescence properties and the quantification of trace elements in pyrite and diopside crystals play a crucial role in the provenance determination of lapis lazuli. The protocol was successfully applied on historical and archaeological objects from Medici's Collection (16 th -18 th century) and from Ancient Egypt (first millennium BC) [25], [26].…”
Section: Lapis Lazulimentioning
confidence: 99%
“…On the basis of the markers found, a protocol was established [25] in which the luminescence properties and the quantification of trace elements in pyrite and diopside crystals play a crucial role in the provenance determination of lapis lazuli. The protocol was successfully applied on historical and archaeological objects from Medici's Collection (16 th -18 th century) and from Ancient Egypt (first millennium BC) [25], [26]. It is not the aim of this paper to report all the markers of the protocol, but as an example diopside crystals of the Afghanistan rocks show higher quantity of titanium (> 710 ppm) or vanadium (>210 ppm) or chromium (>220 ppm) than Tajik samples or a strong ionoluminescence band at about 770 nm.…”
Section: Lapis Lazulimentioning
confidence: 99%